Environmental Management in the Period of Economics Transformation - Čepinskis, Jonas (Ekonomika, 2001)
Concepts of welfare. welfare economics, and welfare State are being used in economic literature more and more frequently. Quality of environment is very important dimension in the conception of modern welfare. It is noteworthy to mention not going deep into complicated and not stable structure of welfare concept that environment is being kept as important component as security, health, and justice. The significance of environment quality became going without saying in developed economics countries.In the period of centralized economics environment quality had more proclaimed meaning that the real one. It is shown that economical activity is being executed without evaluating its influence to environment when stressing environmental defense and just later trying to eliminate negative consequences. It is more purposeful to use concept of “Environmental Use” that covers environmental protection also.There was intensive development of economy in Lithuania during centralized economics period, however economy activities influence upon quality of environment was estimated not enough. Information volume and precision of related data was limited when environment quality decrease. That way of growth of economy should be evaluated as unsustainable development.The processes of economics system transformation have influence on environment use changes also. Transformation of Lithuania’s economic system into free market economy is linked with stabilization of environmental quality and step-bystep improvement. Complication and contradictoriness of transformation process didn’t give any positive changes of environment quality. These processes concurrented with integration processes. Integration into global structures and European Union can’t be separated from sustainable development tendences. Big attention is paid to localization of sustainable development. Main part of development and environment problems are being solved in regional and local levels.Realization of global principles of sustainability is able just with active participating of municipalities. Almost ninety percent activity trying to achieve sustainable development goals is based on decisions of local authority.There are some obstacles trying to localize sustainable development principles. 12 local municipalities of Lithuania overcome on these obstacles also.The object of this research is the changes of Lithuania’s environment use that happens in the motion of economic system transformation. Factors that incentives and disturbs main tendences and reasons are tried to clear up.